Assessment of Adverse Drug Reactions in Geriatric Patients Admitted to a Tertiary Care Teaching Hospital in South India - Mallesh Mandha; Purushothama Reddy K; V J Dawn; P V Soumya; V R Irene; K A Ameena Kadar (Revista Electronica de Veterinaria, 2024)
Assessment of Adverse Drug Reactions (ADRs) in Geriatric patients was carried out in a south Indian tertiary care teaching hospital. Our study focused on the greater susceptibility of geriatric patients to ADRs, which are an important health issues and a leading cause of morbidity. A single-centre prospective observational study was conducted with a total of 227 patients to investigate the occurrence and characteristics of ADRs. Males (58.62%,) were affected more than females (41.38%,). Age, polypharmacy, and Co-morbid diseases were the primary risk factors, accounting for 100%, 100%, and 94.82% respectively. The most significant risk factors identified were hypertension (51.72%), and type II diabetes mellitus (44.82%). The prevalence of ADRs was determined as 25.5% (n=58) with an incidence rate of 6.82%, Odds ratio (0.34, p=0.059) and Relative risk (142.65, p=0.0005). Oral administration of drugs (72.41%) lead to the most ADRs. Antibiotics and Antiplatelets (20.69%) caused the most ADRs such as Constipation (20.68%) by Clopidogrel, Various Reactions from Antibiotics (>17%) followed by Oedema (13.8%) by Prednisolone. Skin and Appendages (32.76%) were implicated by the majority of reactions. Most of the reactions were possible (WHO-UMC Scale - 53.45%), Moderate (Hartwig and Siegel Scale – 31%) and possible (Liverpool Causality Assessment Tool – 60.34%). Clinical pharmacists reported the highest (82.76%) ADRs. Our study contributes to the pharmacovigilance programme of the nation. There is a pressing need of reporting the ADRs and to develop tools to empower healthcare professionals that would significantly decrease the time required for initial assessment of ADRs and related harm.